•   Wikis

# Continuum mechanics/Maxwell relations for thermoelasticity: Wikis

Note: Many of our articles have direct quotes from sources you can cite, within the Wikipedia article! This article doesn't yet, but we're working on it! See more info or our list of citable articles.

# Study guide

Up to date as of January 14, 2010

## Maxwell relations between thermodynamic quantities

For thermoelastic materials, show that the following relations hold:

$\frac{\partial \psi}{\partial \boldsymbol{E}} = \cfrac{1}{\rho_0}~\hat{\boldsymbol{S}}(\boldsymbol{E},T) ~;~~ \frac{\partial \psi}{\partial T} = -\hat{\eta}(\boldsymbol{E},T) ~;~~ \frac{\partial g}{\partial \boldsymbol{S}} = \cfrac{1}{\rho_0}~\tilde{\boldsymbol{E}}(\boldsymbol{S}, T) ~;~~ \frac{\partial g}{\partial T} = \tilde{\eta}(\boldsymbol{S}, T)$

where $\psi(\boldsymbol{E},T)$ is the Helmholtz free energy and $g(\boldsymbol{S},T)$ is the Gibbs free energy.

Also show that

$\frac{\partial \hat{\boldsymbol{S}}}{\partial T} = - \rho_0~\frac{\partial \hat{\eta}}{\partial \boldsymbol{E}} \qquad\text{and}\qquad \frac{\partial \tilde{\boldsymbol{E}}}{\partial T} = \rho_0~\frac{\partial \tilde{\eta}}{\partial \boldsymbol{S}} ~.$

Proof:

Recall that

$\psi(\boldsymbol{E}, T) = e - T~\eta = \bar{e}(\boldsymbol{E}, \eta) - T~\eta ~.$

and

$g(\boldsymbol{S}, T) = - e + T~\eta + \cfrac{1}{\rho_0}~\boldsymbol{S}:\boldsymbol{E} ~.$

(Note that we can choose any functional dependence that we like, because the quantities e, η, $\boldsymbol{E}$ are the actual quantities and not any particular functional relations).

The derivatives are

$\frac{\partial \psi}{\partial \boldsymbol{E}} = \frac{\partial \bar{e}}{\partial \boldsymbol{E}} = \cfrac{1}{\rho_0}~\boldsymbol{S} ~;\qquad \frac{\partial \psi}{\partial T} = - \eta ~.$

and

$\frac{\partial g}{\partial \boldsymbol{S}} = \cfrac{1}{\rho_0}~\frac{\partial \boldsymbol{S}}{\partial \boldsymbol{S}}:\boldsymbol{E} = \cfrac{1}{\rho_0}~\boldsymbol{E} ~;\qquad \frac{\partial g}{\partial T} = \eta ~.$

Hence,

${ \frac{\partial \psi}{\partial \boldsymbol{E}} = \cfrac{1}{\rho_0}~\hat{\boldsymbol{S}}(\boldsymbol{E},T) ~;~~ \frac{\partial \psi}{\partial T} = -\hat{\eta}(\boldsymbol{E},T) ~;~~ \frac{\partial g}{\partial \boldsymbol{S}} = \cfrac{1}{\rho_0}~\tilde{\boldsymbol{E}}(\boldsymbol{S}, T) ~;~~ \frac{\partial g}{\partial T} = \tilde{\eta}(\boldsymbol{S}, T) }$

From the above, we have

$\frac{\partial^2 \psi}{\partial T\partial\boldsymbol{E}} = \frac{\partial^2 \psi}{\partial \boldsymbol{E}\partial T} \qquad\implies\qquad -\frac{\partial \hat{\eta}}{\partial \boldsymbol{E}} = \cfrac{1}{\rho_0}\frac{\partial \hat{\boldsymbol{S}}}{\partial T} ~.$

and

$\frac{\partial^2 g}{\partial T\partial\boldsymbol{S}} = \frac{\partial^2 g}{\partial \boldsymbol{S}\partial T} \qquad\implies\qquad \frac{\partial \tilde{\eta}}{\partial \boldsymbol{S}} = \cfrac{1}{\rho_0}\frac{\partial \tilde{\boldsymbol{E}}}{\partial T} ~.$

Hence,

${ \frac{\partial \hat{\boldsymbol{S}}}{\partial T} = - \rho_0~\frac{\partial \hat{\eta}}{\partial \boldsymbol{E}} \qquad\text{and}\qquad \frac{\partial \tilde{\boldsymbol{E}}}{\partial T} = \rho_0~\frac{\partial \tilde{\eta}}{\partial \boldsymbol{S}} ~. }$

## More Maxwell relations

For thermoelastic materials, show that the following relations hold:

$\frac{\partial \hat{e}(\boldsymbol{E},T)}{\partial T} = T~\frac{\partial \hat{\eta}}{\partial T} = -T~\frac{\partial^2 \hat{\psi}}{\partial T^2}$

and

$\frac{\partial \tilde{e}(\boldsymbol{S},T)}{\partial T} = T~\frac{\partial \tilde{\eta}}{\partial T} + \cfrac{1}{\rho_0}~\boldsymbol{S}:\frac{\partial \tilde{\boldsymbol{E}}}{\partial T} = T~\frac{\partial^2 \tilde{g}}{\partial T^2} + \boldsymbol{S}:\frac{\partial^2 \tilde{g}}{\partial \boldsymbol{S}\partial T}~.$

Proof:

Recall,

$\hat{\psi}(\boldsymbol{E},T) = \psi = e - T~\eta = \hat{e}(\boldsymbol{E}, T) - T~\hat{\eta}(\boldsymbol{E}, T)$

and

$\tilde{g}(\boldsymbol{S},T) = g = - e + T~\eta + \cfrac{1}{\rho_0}~\boldsymbol{S}:\boldsymbol{E} = -\tilde{e}(\boldsymbol{S}, T) + T~\tilde{\eta}(\boldsymbol{S}, T) + \cfrac{1}{\rho_0}~\boldsymbol{S}:\tilde{\boldsymbol{E}}(\boldsymbol{S}, T)~.$

Therefore,

$\frac{\partial \hat{e}(\boldsymbol{E},T)}{\partial T} = \frac{\partial \hat{\psi}}{\partial T} + \hat{\eta}(\boldsymbol{E}, T) + T~\frac{\partial \hat{\eta}}{\partial T}$

and

$\frac{\partial \tilde{e}(\boldsymbol{S},T)}{\partial T} = - \frac{\partial \tilde{g}}{\partial T} + \tilde{\eta}(\boldsymbol{S},T) + T~\frac{\partial \tilde{\eta}}{\partial T} + \cfrac{1}{\rho_0}~\boldsymbol{S}:\frac{\partial \tilde{\boldsymbol{E}}}{\partial T} ~.$

Also, recall that

$\hat{\eta}(\boldsymbol{E},T) = -\frac{\partial \hat{\psi}}{\partial T} \qquad \implies \qquad \frac{\partial \hat{\eta}}{\partial T} = -\frac{\partial^2 \hat{\psi}}{\partial T^2} ~,$
$\tilde{\eta}(\boldsymbol{S}, T) = \frac{\partial \tilde{g}}{\partial T} \qquad \implies \qquad \frac{\partial \tilde{\eta}}{\partial T} = \frac{\partial^2 \tilde{g}}{\partial T^2} ~,$

and

$\tilde{\boldsymbol{E}}(\boldsymbol{S}, T) = \rho_0~\frac{\partial \tilde{g}}{\partial \boldsymbol{S}} \qquad \implies \qquad \frac{\partial \tilde{\boldsymbol{E}}}{\partial T} = \rho_0~\frac{\partial^2 \tilde{g}}{\partial \boldsymbol{S}\partial T}~.$

Hence,

${ \frac{\partial \hat{e}(\boldsymbol{E},T)}{\partial T} = T~\frac{\partial \hat{\eta}}{\partial T} = -T~\frac{\partial^2 \hat{\psi}}{\partial T^2} }$

and

${ \frac{\partial \tilde{e}(\boldsymbol{S},T)}{\partial T} = T~\frac{\partial \tilde{\eta}}{\partial T} + \cfrac{1}{\rho_0}~\boldsymbol{S}:\frac{\partial \tilde{\boldsymbol{E}}}{\partial T} = T~\frac{\partial^2 \tilde{g}}{\partial T^2} + \boldsymbol{S}:\frac{\partial^2 \tilde{g}}{\partial \boldsymbol{S}\partial T}~. }$